2016
DOI: 10.1161/strokeaha.116.013266
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Desaturation in the Stroke Unit Is Associated With Wake-Up Ischemic Stroke

Abstract: Background and Purpose-Wake-up stroke (WUS) represents a quarter of all ischemic strokes and may be a specific subgroup. Nocturnal desaturation secondary to sleep-disordered breathing is an independent risk factor for stroke, but the association between nocturnal desaturation and WUS remains unclear. We investigated the relationship between nocturnal desaturation using oxygen desaturation index and WUS in patients with acute stroke in the stroke unit. Methods-A total of 298 patients admitted for acute ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
6
14
0
Order By: Relevance
“…To our knowledge, this is the first report to describe the proportion of WUS cases and examine differences in clinical characteristics and functional outcomes between WUS and non-WUS patients in the Chinese population. The finding that WUS accounted for 27.9% of ischemic strokes is consistent with conclusions from the International Stroke Trial and Canadian Stroke Registry [12] and other previous series [7,11,30]. Although controversy remains, our findings were also consistent with previous studies that reported similar distributions of risk factors, stroke severity, and TOAST classifications between cases of WUS and non-WUS [10,11,17,30,31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, this is the first report to describe the proportion of WUS cases and examine differences in clinical characteristics and functional outcomes between WUS and non-WUS patients in the Chinese population. The finding that WUS accounted for 27.9% of ischemic strokes is consistent with conclusions from the International Stroke Trial and Canadian Stroke Registry [12] and other previous series [7,11,30]. Although controversy remains, our findings were also consistent with previous studies that reported similar distributions of risk factors, stroke severity, and TOAST classifications between cases of WUS and non-WUS [10,11,17,30,31].…”
Section: Discussionsupporting
confidence: 92%
“…The finding that WUS accounted for 27.9% of ischemic strokes is consistent with conclusions from the International Stroke Trial and Canadian Stroke Registry [12] and other previous series [7,11,30]. Although controversy remains, our findings were also consistent with previous studies that reported similar distributions of risk factors, stroke severity, and TOAST classifications between cases of WUS and non-WUS [10,11,17,30,31]. Lundholm et al [31] reported that WUS patients more frequently had previous stroke, which is also in accordance with our conclusion.…”
Section: Discussionsupporting
confidence: 91%
“…A study in a South Korean stroke unit showed that nearly 30% of persons with WUS compared to just 12% of those with non-WUS had frequent nocturnal desaturation. 22 Patients with WUS appear to have similar age and gender distribution as those with non-WUS. 6 Mechanisms of WUS Analysis of International Stroke Trial data of over 17,000 acute ischemic strokes showed that WUS was more likely to occur by a lacunar mechanism and less likely to occur through a large vessel anterior circulation mechanism.…”
Section: Risk Factors For Wusmentioning
confidence: 89%
“…85 Evidence further suggests that severe OSA and severe hypoxemia occur with increased frequency in patients with WUS compared non-WUS. 18,22 In WUS, OSA may be directly related to the mechanism of stroke and it may be particularly important in these patients to conduct polysomnography to rule out OSA. Furthermore, severe hypoxemia in OSA can only be detrimental in the setting of a new stroke and may in part account for neurologic worsening and poor functional and cognitive outcomes, which are known to occur at higher rates when OSA co-occurs with stroke.…”
Section: Mri-guided Clinical Trialsmentioning
confidence: 99%
“…There are several reports of dyslipidemia being more frequent in WUS. 13 14 15 Lower blood pressure was suggested as a risk factor for WUS, 11 but this finding has not been replicated in other studies. Four 12 15 16 17 of six 11 12 13 15 16 17 studies that assessed OSA as a stroke risk factor found that habitual snoring or a higher apnea-hypopnea index in poststroke polysomnography (PSG) was more frequent among WUS patients ( Supplementary Table 1 in the online-only Data Supplement).…”
Section: Introductionmentioning
confidence: 85%